2012
DOI: 10.1021/jf2042517
|View full text |Cite
|
Sign up to set email alerts
|

Grape Contribution to Wine Aroma: Production of Hexyl Acetate, Octyl Acetate, and Benzyl Acetate during Yeast Fermentation Is Dependent upon Precursors in the Must

Abstract: Wine is a complex consumer product produced predominately by the action of yeast upon grape juice musts. Model must systems have proven ideal for studies of the effects of fermentation conditions on the production of certain wine volatiles. To identify grape-derived precursors to acetate esters, model fermentation systems were developed by spiking precursors into model must at different concentrations. Solid-phase microextraction-gas chromatgraphy mass spectrometry analysis of the fermented wines showed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 47 publications
(73 reference statements)
7
95
3
1
Order By: Relevance
“…Both the concentration and the sensory impact of C 6 compounds are known to decrease in wine when compared to grape juice. Indeed, the highly odor-active C 6 aldehydes found in grape juice are reduced to alcohol during winemaking, whereas specific C 6 compounds are transformed into desirable esters and acetates [26]. C 6 compounds from grapes may therefore contribute to fruity notes in wine [26].…”
Section: Compounds and Other Fadpmentioning
confidence: 99%
“…Both the concentration and the sensory impact of C 6 compounds are known to decrease in wine when compared to grape juice. Indeed, the highly odor-active C 6 aldehydes found in grape juice are reduced to alcohol during winemaking, whereas specific C 6 compounds are transformed into desirable esters and acetates [26]. C 6 compounds from grapes may therefore contribute to fruity notes in wine [26].…”
Section: Compounds and Other Fadpmentioning
confidence: 99%
“…The presence of skins during fermentation could have favoured the availability of different aromaprecursor amino acids, therefore influencing the wine's final volatile composition (Styger et al, 2011). In addition, the presence in skin contact wines of higher available assimilable nitrogen levels could influence yeast CO 2 production, which also might cause an important volatilisation with CO 2 evolution during fermentation (Dennis et al, 2012). However, the loss of volatile compounds through volatilisation could not account for the total loss of volatile compounds, such as terpenes or esters, observed in this study.…”
Section: Effect Of Skin Contact On the Chemical And Sensory Profile Omentioning
confidence: 99%
“…[12] The concentration of these volatile compounds changes with grape variety, environmental conditions, cultural techniques, grape maturity state, and winemaking and ageing techniques. [13][14][15] It has been reported that rain-shelter cultivation effectively delayed the maturation of grape berries, [3,16] slowed sugar accumulation by reducing photosynthetically active radiation (PAR), increased berry and cluster weight, and improved economic returns. [17] During the past several decades, although rain-shelter cultivation has been studied for its commercial value on table grapes and other fruits, [4,[17][18][19] few studies have focused on wine grapes and wine.…”
Section: Introductionmentioning
confidence: 99%